Decolonial Critique to Paulo Freire: The Look of Catherine Walsh - Bolo Romero, Karla (2019)
The following paper addresses the "pedagogy of the oppressed" under the notion of rethinking/relearning/unlearning from a Decolonial perspective, in the form of contributions made by Catherine Walsh to the work of Paulo Freire. Specific criticisms will be highlighted, such as 1) the critique of the relationality of Paulo Freire's environment-political struggle and the specific context of the resistance of educational practices in AbyaYala. 2) We analyze the way in which C. Walsh poses the re-thinking of the concept of criticality in the liberating pedagogical process. And, lastly, we examine 3) The re-approach of transformative / liberating pedagogies.